Applicability of RPMI 2650 and Calu-3 Cell Models for Evaluation of Nasal Formulations - Nadica Sibinovska; Simon Žakelj; Jurij Trontelj; Katja Kristan (MDPI AG, 2022)
The RPMI 2650 and Calu-3 cell lines have been previously evaluated as models of the nasal and airway epithelial barrier, and they have demonstrated the potential to be used in drug permeation studies. However, limited data exist on the utilization of these two cell models for the assessment of nasal formulations. In our study, we tested these cell lines for the evaluation of in vitro permeation of intranasally administered drugs having a local and systemic effect from different solution- and suspension-based formulations to observe how the effects of formulations reflect on the measured in vitro drug permeability. Both models were shown to be sufficiently discriminative and able to reveal the effect of formulation compositions on drug permeability, as they demonstrated differences in the in vitro drug permeation comparable to the in vivo bioavailability. Good correlation with the available bioavailability data was also established for a limited number of drugs formulated as intranasal solutions. The investigated cell lines can be applied to the evaluation of in vitro permeation of intranasally administered drugs with a local and systemic effect from solution- and suspension-based formulations.